2017
DOI: 10.1186/s12885-016-2998-2
|View full text |Cite
|
Sign up to set email alerts
|

Chemotherapy-induced Sinusoidal Injury (CSI) score: a novel histologic assessment of chemotherapy-related hepatic sinusoidal injury in patients with colorectal liver metastasis

Abstract: BackgroundPreoperative neoadjuvant therapy for colorectal liver metastases (CRLM) is increasing in use and can lead to chemotherapy-induced damage to sinusoidal integrity, namely sinusoidal obstruction syndrome (SOS). SOS has been associated with an increased need for intraoperative blood transfusions, increased length of hospitalization post-surgery, decreased tumor response, and a shorter overall survival after resection due to liver insufficiency. It is critical for clinicians and pathologists to be aware o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
30
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 34 publications
2
30
0
Order By: Relevance
“…(3) Aberrant CD34 expression has been used as a measure of severity of oxaliplatin-induced liver injury and sinusoidal obstruction syndrome. (4) In our case, the sinusoidal expression pattern of CD34 suggests a similar mechanism to oxaliplatin-induced endothelial damage. Regardless of the mechanism of drug-induced liver injury, immune-related adverse events with PD-1 inhibitors are highly idiosyncratic and necessitate an individualized approach to management.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…(3) Aberrant CD34 expression has been used as a measure of severity of oxaliplatin-induced liver injury and sinusoidal obstruction syndrome. (4) In our case, the sinusoidal expression pattern of CD34 suggests a similar mechanism to oxaliplatin-induced endothelial damage. Regardless of the mechanism of drug-induced liver injury, immune-related adverse events with PD-1 inhibitors are highly idiosyncratic and necessitate an individualized approach to management.…”
Section: Discussionsupporting
confidence: 60%
“…The commonly used chemotherapeutic, oxaliplatin, is linked with sinusoidal obstruction syndrome and NRH, whereby increased expression of the endothelial cell marker, CD34, is associated with a loss of fenestrae in the sinusoidal endothelium, a process known as sinusoidal capillarization . Aberrant CD34 expression has been used as a measure of severity of oxaliplatin‐induced liver injury and sinusoidal obstruction syndrome . In our case, the sinusoidal expression pattern of CD34 suggests a similar mechanism to oxaliplatin‐induced endothelial damage.…”
Section: Discussionmentioning
confidence: 55%
“…Several studies have demonstrated early diagnosis or prediction of VOD/SOS with this method, before the appearance of conventional clinical criteria [74][75][76]. Other proposed methods involve the multifactorial, or panel, scoring approach for early diagnosis or prediction of VOD/SOS with the use of ultrasound [77][78][79][80]. Independent predictors of VOD/SOS that may enhance ultrasound diagnosis include gallbladder wall thickening and paraumbilical vein blood flow [78,80].…”
Section: New Diagnostic Techniques/parametersmentioning
confidence: 99%
“…Independent predictors of VOD/SOS that may enhance ultrasound diagnosis include gallbladder wall thickening and paraumbilical vein blood flow [78,80]. Proposed methods aimed at diagnosis or prediction specifically of chemotherapy-induced VOD/SOS include a score consisting of expression of CD34 cells, increased levels of smooth muscle actin, and aberrant expression of glutamine synthetase [79]. The use of contrast-enhanced computed tomography also has been suggested to detect multiple factors such as clover-like sign, peripheral distribution of heterogeneity, increased spleen volume, and hepatic parenchyma, which were found to be independent predictors of VOD/SOS via this method [77,81,82].…”
Section: New Diagnostic Techniques/parametersmentioning
confidence: 99%
“…This difference may reflect the hepatic venous pressure gradient and parenchymal stiffness, and the increasing rate of SOS is associated with morbidity after liver resection. Rate of increase in splenic volume and decrease in platelet count are predictive of SOS . Reportedly, 75% of patients who received adjuvant chemotherapy had increased splenic volume and 40% of patients did not recover after discontinuation of chemotherapy .…”
Section: Chemotherapy‐associated Liver Damagementioning
confidence: 99%